Impact of Canopy Cover on Butterfly Abundance and Diversity in Intermediate Zone Forest of Sri Lanka - B.M.B Weerakoon; A.M.R.S. Bandara; K.B. Ranawana (Journal of Tropical Forestry and Environment, 2015)
This study was designed to identify the influence of canopy cover on butterfly abundance in young secondary forest and regenerating forest at Maragamuwa area of Kumaragala forest reserve in Naula, Matale district of Sri Lanka. Line transect method was used to collect data. Hundred meter long five transects were established in each forest area. Butterfly abundance data were collected weekly for eight months from January to August 2014. Regenerating forest had low canopy cover (<50%) than young secondary forest (20-90%). Total of 2,696 butterflies belonging to 87 species in six families were recorded. Some butterfly species were restricted to shady areas, but most butterflies were abundant in sunny areas. Butterflies in some families (Family Lycanidae, Nymphalidae, Pieridae) were abundant in sunny conditions and some families (Family Hesperiidae, Papilionidae) abundant in shade. ANOVA was conducted to identify the variation of number of species (F=54.05, p<0.001) and among abundance (F=10.49, p<0.05) with the canopy cover. Species richness was high in moderate canopy cover (20±5%). Negative Pearson correlation coefficient stated butterfly abundance decreased with the canopy cover (r=-0.91) and species richness decreased with canopy cover (r=-0.85). Some butterflies were common in sunny areas and some species were confined to shady areas. However, most of the species were generally found throughout the area. Regenerating forest encountered more shrubs than in young secondary forest, which butterflies preferred to food on. Main findings of the study were that butterfly abundance was high in sunny areas and butterfly species richness was high in moderate shady areas.